Factors Affecting the Status of Precarious Employees among Young Workers in the Formal Sector in Central Java Province 2024 - Ratih Restiani; Ekaria (Jurnal Ketenagakerjaan, 2026)
The process of job informalization is a condition in which the previously stable formal sector is now increasingly resembling the informal sector, which lacks job security and offers low wages. This phenomenon is consistent with precarious employment, which refers to jobs that lack job stability, social security, and decent income. Young people tend to have limited skills and work experience. This forces young people to accept precarious employment as their only option. This study aims to provide an overview and to identify and analyze the social factors, experiences, and skills of individuals, as well as the socio-economic factors of regencys/cities that influence the precarious employment status among young workers in the formal sector in Central Java in 2024. The data used is sourced from the August 2024 Sakernas survey. The analysis method employed is multilevel binary logistic regression. The results of the study indicate that variables related to experience and skills factor, such as educational level, participation in training, and job tenure, moreover social factor such as marital status, occupation, and union membership, as well as the regional minimum wage (UMK) from socioeconomic factors, significantly influence the precarious employment status of young workers in the formal sector in Central Java Province in 2024.